Managing challenging situations in the coach-athlete dyad: introducing the grey zone model from the coach perspective - Slade, K.; Jowett, S.; Rhind, D. (International Sport Coaching Journal, 2025)
Challenging situations and interactions are necessary and unavoidable in sport. From deselection to injury, burnout, and mental health issues, coaches and athletes will face challenging situations throughout their sporting career. The aims of this research study were to (a) introduce a conceptual model of challenging situations and subsequently to (b) explore a range of challenging situations that occur in high-performance sport, and (c) discover how such challenging situations are managed and perceived by high-performance coaches. In this study, challenging situations in coach-athlete dyads are defined as organisational, performance, interpersonal, and personal stressors that can push or pull one or both the coach and athlete, and subsequently their relationship into a state of indeterminacy (i.e., the Grey Zone) that may cause stress, strain, conflict, or resolution and understanding depending on how the challenging situations are managed. A total of 11 current high-performance and World Class Performance coaches (M = 41.64 years old, SD = 10.69 years; female = 4, male = 7), took part in a semistructured interview aided by vignettes to explore and discover the process by which coaches deal with challenging situations. Using a pragmatism approach, a content analysis guided by the conceptual Grey Zone Model was utilised to analyse the obtained qualitative data. Results indicated that coaches regularly experience challenging situations and use a variety of techniques to manage them. The Grey Zone Model is proposed as a practical tool to help coaches, athletes, and other practitioners, such as sport psychology consultants and coach developers to analyse the various phases of challenging situations.